2006
DOI: 10.1590/s0100-879x2006001000005
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation from an alternative stem cell source in Fanconi anemia patients: analysis of 47 patients from a single institution

Abstract: We transplanted 47 patients with Fanconi anemia using an alternative source of hematopoietic cells. The patients were assigned to the following groups: group 1, unrelated bone marrow (N = 15); group 2, unrelated cord blood (N = 17), and group 3, related non-sibling bone marrow (N = 15). Twenty-four patients (51%) had complete engraftment, which was not influenced by gender (P = 0.87), age (P = 0.45), dose of cyclophosphamide (P = 0.80), nucleated cell dose infused (P = 0.60), or use of anti-T serotherapy (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
2
11
0
1
Order By: Relevance
“…The primary cause of mortality in our study was GVHD (4 acute and 1 chronic) and infection which is comparable to former studies 17. Guardiola et al suggested that the effect of on mortality is not confined to severe acute GVHD in the first post-transplant months and it also probably by inducing chronic GVHD can be a risk factor for development of secondary malignancies, particularly in patients transplanted with peripheral blood 7,18.…”
Section: Discussionsupporting
confidence: 89%
“…The primary cause of mortality in our study was GVHD (4 acute and 1 chronic) and infection which is comparable to former studies 17. Guardiola et al suggested that the effect of on mortality is not confined to severe acute GVHD in the first post-transplant months and it also probably by inducing chronic GVHD can be a risk factor for development of secondary malignancies, particularly in patients transplanted with peripheral blood 7,18.…”
Section: Discussionsupporting
confidence: 89%
“…5,10,12,24 Graft rejection, regimen-related toxicity and high risk of GVHD have been reported to be the greatest obstacles to successful outcome in patients with FA given HSCT from an UD.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of identifying these patients and the lack of studies conducted in Brazil mainly focused on their clinical characteristics (10)(11)(12)(13)(14)(15) , the objective of the present study was to characterize the clinical profile of patients diagnosed with FA seen at a clinical genetics department.…”
Section: Introductionmentioning
confidence: 99%